Main features of the labour policy in Portugal - Moniz, António Brandão (2008)
In this working paper is presented information on the Portuguese labour market developed with the support of the European project WORKS-“Work organisation and restructuring in the knowledge society”. Is still a on the process article and thus commentaries are welcome. The structure is based on the following topics: a) The employment policy (Time regimes - time use, flexibility, part-time work, work-life balance -, and the work contracts regimes – wages, contract types, diversity); b) Education and training (skilling outcomes, rules on retraining and further training, employability schemes, transferability of skills); c) Equal opportunities (relevance of equal opportunity regulation for restructuring outcomes, the role of gender and age regulation); d) Restructuring effects (policy on transfer of personnel, policy on redundancies, and participation or voice in restructuring).